Project BRAHSS: behavioural response of Australian humpback whales to seismic surveys. - Cato, Douglas; Noad, Michael; Dunlop, Rebecca; McCauley, Robert; Gales, Nick; Salgado-Kent, Chandra; Kniest, Hendrik; Paton, David; Jenner, Curt; Noad, John; Maggi, Amos; Parnum, Iain; et al. (Acoustical Society of Australia, 2012)
BRAHSS is a major project aimed at understanding how humpback whales respond to noise, particularly from seismic air gun arrays. It also aims to infer the longer term biological significance of the responses from the results and knowledge of normal behaviour. The aim is to provide the information that will allow seismic surveys to be conducted efficiently with minimal impact on whales. It also includes a study of the response to ramp-up in sound level. Ramp-up is widely used at the start of operations as a mitigation measure intended to cause whales to move away, but there is little information to show that it is effective. BRAHSS involves four experiments with migrating humpback whales off the east and west coasts of Australia with noise exposures ranging from a single air gun to a full seismic array. Two major experiments have been completed off the east coast, the second involving 70 scientists. Whale movements were tracked using theodolites on two high points ashore and behavioural observations were made from these points and from three small vessels and the source vessel. Vocalising whales were tracked underwater with an array of hydrophones. These and other moored acoustic receivers recorded the sound field at several points throughout the area. Tags (DTAGs) were attached to whales with suction caps for periods of several hours. Observations and measurements during the experiments include the wide range of variables likely to affect whale response and sufficient acoustic measurements to characterise the sound field throughout the area. The remaining two experiments will be conducted further off shore off the west coast in 2013 and 2014.